Strategic Framework for New Electric Power System Development under the Energy Security Pattern - Tang Guangfu; Zhou Jing; Pang Hui; Lin Junjie; Fan Zheng; Wu Yanan; He Zhiyuan; Ma Shicong; Xue Feng; Zhou Baorong (中国工程科学, 2023)
The construction of a new electric power system is the key path to achieve the carbon peaking and carbon neutrality goals and ensure energy transition security. As the largest man-made system that is complex and highly nonlinear, the electric power system is the core of future energy transition. However, the security of the electric power system faces severe challenges owing to the volatility and randomness of new energy power generation. Considering the new situation and challenges faced by the energy transition security in China, this study clarifies the implications of energy security in terms of supply, environment, economy, and technology, investigates the development goals and strategic paths for energy transformation, and explores the significance of the new electric power system to energy security. The key factors of power source, power grid, load, energy storage, market, and technology that affect the new electric power system security are analyzed. According to the study, the core systems required for the security development of the new electric power system should be constructed from three aspects: emergency warning, sharing and mutual aid, and security defense. Furthermore, the basic idea for the research on the new electric power system development path is proposed to provide a basic reference for the new electric power system construction and the security development research.